An evidence-based review of the outcome of fulvestrant plus a targeted agent versus fulvestrant alone in treating hormone receptor-positive endocrine therapy-resistant metastatic breast cancer - Hua, Yu-Ming (Archives of gynecology and obstetrics, 2019)
Background Fulvestrant is approved for the hormone receptor-positive advanced metastatic breast cancer (MBC) patients during or after prior endocrine treatment. The adding of a targeted agent to fulvestrant has improved the outlook for these patients from recent studies. However, these results were still under investigation, the analysis was undertaken to assess the clinical outcomes of the fulvestrant-based combination therapy compared with fulvestrant monotherapy. Methods I systematically searched electronic databases to identify eligible literatures till January 2019. Randomized-controlled trials (RCTs) assessing the efficacy of a targeted agent to fulvestrant with fulvestrant mono-therapy in MBC patients who are refractory to or intolerant of prior endocrine therapy were included. Results Six RCTs were included in this analysis. The group of a targeted agent to fulvestrant was significantly improved overall survival (OR = 0.86, 95%CI = 0.76–0.97, P = 0.02), progression-free survival (OR = 0.66, 95%CI = 0.54–0.81, P < 0.0001), as well with the objective response rate (OR = 2.30, 95%CI = 1.67–3.18, P < 0.00001), respectively. However, there are more adverse effects with the combination group (OR = 6.71, 95%CI = 5.58–8.06, P < 0.00001). Conclusions Pooled results indicate that adding a targeted agent to fulvestrant prolonged OS, PFS and ORR in relapse or metastatic hormone receptor-positive breast cancer after prior endocrine therapy. Combination of fulvestrant with a targeted agent was associated with more frequent grade 3/4 toxicities. Further research is needed to develop a database of reliable biomarkers and their individual impact on the fulvestrant-based combination treatments.